The Effectiveness of the Health Promotion Model (Promkes) Based on the Transtheory Model on Pre-Eclampsy Prevention Behavior in Pregnant Women - Sugijati Sugijati; Jamhariyah Jamhariyah; Ida Prijatni (Journal of Social Science, 2023)
Pre-eclampsia is a disease during pregnancy that often occurs and needs serious treatment. Since 2012 - 2016 pre-eclampsy has been ranked 1st cause of MMR in East Java, pre-eclampsia cases (2016) amounted to 30.90% (East Java Provincial Health Office, 2016). Data from Kalisat health center January - April the number of pregnant women at risk of pre-eclampsy amounted to 193 with the number of pre-eclampsic pregnant women at 35 people, as well as at the Sumberjambe health center there were 268 people at risk of pre-eclampsia, 18 people pre-eclampsia. This research is a continuation of phase 1 research entitled health promotion model (promkes) midwives in pre-eclampsia pregnant women based on stage of change. The purpose of the study was to test the effectiveness of the health program model in pre-eclampsia pregnant women based on the transtheory model. The design of this study was quasi-experimental. Sampling using simple random sampling technique of 60 respondents. Instruments with questionnaire sheets and promkes models. SPSS test analysis obtained p values (0.000) < α ( 0.05) at all stages, so Ho was rejected. There are differences before and after the health program is innovated. The need to add an innovative health promotion model to change the behavior of pregnant women.